UPAYA MENINGKATKAN KEMAMPUAN MENULIS NASKAH DRAMA MELALUI PENDEKATAN PROSES PADA SISWA KELAS VIII SMP PGRI 3 BANDAR LAMPUNG - Lainari, Lainari (LPPM STKIP PGRI Bandar Lampung, 2015)
Learning to write with a process approach not only gives the task of writing and assessing student writing, but also guide the learner in the process of writing. Process approach in teaching playwriting focuses on the process of producing a play. This study aims to determine the increase in the ability to write plays in learning Indonesian language and literature through a process approach in class VIII SMP PGRI 3 Bandar Lampung.This study includes classroom action research (classroom action research) data collection techniques preformance of this research are: Mechanical tests, observations, interviews, and documentation.Based on the results of research and discussion, it can be concluded that through a process approach can improve the writing skills of students in learning playwriting class VIII SMP PGRI 3 Bandar Lampung. Improved most increased is the aspect of the background and the text side, reaching 38.80%. This increase is calculated from prior to the action (initial test) to be taken first cycle and second cycle. While scores of students also increased. In the first cycle the average scores of students amounted to 80.88. This cycle has been an increase of 24.22 or 67% compared with the prior held the action / early tests. In the second cycle also occurs a significant improvement with the average final score of the students was 88.44. thus there has been increased by 7:56 or 21%.